Marx e a História em Ruy Fausto - Prado, Carlos (Revista Espaço Acadêmico, 2010)
Resumo: O objetivo desse artigo é expor as considerações de Fausto sobre a problemática da história em Marx. Fausto escreve em sua Lógica e política importantes considerações sobre o tema, afirmando que Marx não deixou uma filosofia da história, tampouco uma teoria da história, mas apenas uma apresentação da história. Na qual Fausto identifica três modelos: História da liberdade; História da riqueza e História da satisfação. Palavras-chave: História; Dialética, modelos. Abstract: The objective of this article is to expose Fausto’s considerations around the questions in Marx’ history. Fausto writes his Logic and Politic in important considerations around the issue, affirming that Marx hasn’t left a philosophy of the history, neither a theory of the history, but simply a presentation of the history. In witch Fausto identify three patterns: History of the freedom; History of the wealth and History of the satisfaction. Key-word: History; Dialectic, patterns.